The relationship between psychological well-being and academic stress among final year students - Rimonda, Rubi; Fanonta, Muliane; Firdauz Saputra, Firman; Harahap, Laila Apriani Hasanah; Paradhiba, Meutia; Fadillah, Mardi; Siahaan, Perry Boy Chandra; Syam, Nasrianti; Duana , Maiza (Universitas Islam Negeri Raden Intan Lampung, 2025)
Final-year students at Teuku Umar University often experience stress while writing their thesis. This study examined the relationship between psychological well-being (PWB) and academic stress using a cross-sectional design. A total of 93 students from six faculties participated. PWB was measured with the Ryff Psychological Well-Being scale, and academic stress was assessed using the DASS-42 stress subscale. Results showed that 57% of students had high PWB, especially in personal growth, while 57% experienced moderate stress and 13% reported severe stress. On average, PWB scores were 78.7 ± 7.8 and stress scores were 33.9 ± 7.5. Students with higher PWB generally had lower stress, but some still felt pressured due to deadlines, workload, or family responsibilities. Support from supervisors, friends, and family helped, along with personal coping strategies like time management and short breaks. Overall, strong PWB can reduce stress but does not remove it completely, highlighting the need for both personal effort and institutional support during the thesis-writing period.